Lubricity potentials of Azadirachta indica (neem) oil and Cyperus esculentus (tiger nut) oil extracts and their blends in machining of mild steel material - Ignatius Echezona Ekengwu; Ikechukwu Geoffrey Okoli; Obiora Clement Okafor; Obiora Nnaemeka Ezenwa; Joseph Chikodili Ogu (Heliyon)
Friction amongst the cutting tool and workpiece in metal machining produces heat that reduces tool life and workpiece integrity. Consequently, non-biodegradable soluble mineral oil is predominantly used as a lubricant to enhance machining operations. Nevertheless, recent investigations focus on environmentally friendly biodegradable oils for lubrication. Therefore, this study examines the lubricity potential of neem oil, tiger nut oil, and their blends in machining mild steel. It also evaluates the performance characteristics of individual bio-oils and their blends against conventional soluble mineral oil and dry-drilling methods. Neem and tiger nut oils were extracted using pressing and solvent methods, followed by an analysis of their physiochemical properties. The experimental design utilized the I-Optimal custom design and simplex lattice design (SLD) for the individual and blended oils respectively. Response Surface Methodology (RSM) was applied for optimization, with feed rate, oil type, and spindle speed as independent variables, and cutting temperature, surface finish, depth of cut, chip thickness, chip thickness ratio, cutting speed, and material removal rate as response variables. The optimal cutting conditions were predicted at a spindle speed of 695 rpm, feed rate of approximately 0.4735, and neem oil being the cutting fluid. The predicted response values were cutting temperature - 33.5 °C, surface roughness - 2.65 μm, depth of cut - 41.4825 mm, chip thickness - 0.18951 mm, chip thickness ratio - 269.586, cutting speed - 17.4695 m/min, and material removal rate - 2.38025E-05. Results indicated neem oil surpassed tiger nut oil and conventional oils in minimizing cutting temperatures and enhancing surface quality, achieving a desirability value of 0.85428 under optimal conditions. Moreover, an 80/20 blend of neem and tiger nut oils exhibited improved performance, attaining a desirability value of 0.992, underscoring its potential as an effective cutting fluid. The findings advocate for the use of bio-based cutting fluids in machining operations, indicating environmental and economic advantages while promoting future research into alternative agro-based solutions. However, limitations regarding material applicability and the necessity for further investigation into the micro-structural effects of cutting fluids on diverse engineering materials are acknowledged.